Aspirin for Primary Stroke Prevention; Evidence for a Differential Effect in Men and Women - Gdovinova, Zuzana; Kremer, Christine; Lorenzano, Svetlana; Dawson, Jesse; Lal, Avtar; Caso, Valeria (Frontiers in Neurology, 2022)
Background: The use of aspirin for primary prevention of cardiovascular events in men and women remains controversial. Our study aimed to investigate the role of aspirin in primary stroke prevention in men and women and the effect of aspirin on risk of ischemic stroke in patients with covert cerebral small vessel disease (ccSVD). Methods We performed systematic searches of the PubMed, and Cochrane Library databases, covering the period from the inception of each database to May 2021. The incidence of any ischemic stroke (IS) or hemorrhagic stroke (HS) was the main outcome. The incidence of stroke overall, both ischemic (IS) and hemorrhagic (HS), was the main outcome. Results From 531 abstracts, 11 randomized control trials which assessed primary prevention of cardiovascular events in men and women were included. Only one study assessed the risk of aspirin in people with ccSVD. In women, there was significant decrease in the risk of stroke (OR 0.85 [95% CI 0.73, 0.99], p = 0.03) and IS (OR 0.76 [0.63, 0.93], p = 0.008) with aspirin compared to placebo while no increase in the risk of HS was found (OR 1.78 [0.61, 5.19], p = 0.29). In men, aspirin did not affect the risk of stroke (OR 1.13 [0.97, 1.31], p = 0.12) and IS (OR 0.94 [0.67, 1.32], p = 0.72) but increased the risk of HS with borderline statistical significance (OR 1.99 [0.99, 4.03], p = 0.05) compared to placebo. Aspirin significantly increased major bleedings in both sexes (p < 0.05). We found no evidence to support the use of aspirin in patients with ccSVD. Conclusion Our meta-analysis suggests aspirin is effective in primary prevention of stroke and IS in women with no clear increased risk of HS. However, it was associated with an overall increased risk of bleeding. Aspirin is not recommended in ccSVD.